Developing a Philippine climate-ocean typology as input to national vulnerability assessments - David, Laura T. (Animo Repository, 2015)
Remotely-sensed information was utilized to naturally divide the archipelagic waters of the Philippines into distinct clusters of historical air-sea climate exposures. For data, we made use of satellite-derived Sea surface temperature (SST), and sea surface height (SSH), wind data (W), and precipitation (P). Results show that the Philippines naturally divide into 11 exposure clusters. Within each cluster the trends and anomalies of SST, anomalies and future scenarios of precipitation, and trends of sea surface height (SSH) were further calculated. Results were then compared amongst the clusters and against global statistics to gain insight on the behavior in each of the clusters. Analysis shows that the entire Philippines suffer twice to 3-times the magnitude of the global sea level rise. The northwestern (cluster II) and the tip of the northeastern (cluster X) coastal and marine areas of the Philippines are most prone to extreme temperature and precipitation hazards. In comparison the south Sulu Sea (cluster XI) and Sulawesi (cluster VI) are the sites with the lowest magnitude of air-sea hazards. So far, these hazard typologies has serve as input to the Philippine I-C-SEA-Change tool built to guide non-specialists in local and adaptive capacity assessments.